Continuing Education for Men - Ladan, C. J.; Crooks, Maxine M. (Canadian Journal of Counselling and Psychotherapy, 2012)
The characteristics, motives and goals of twenty-two mature male students are compared to those of an age-matched sample of mature women continuing their education. It was hypothesized that similarities between their objectives, their reasons for continuing education and the obstacles they faced would be noted. However, results showed that each group chose goals in accord with sex stereotypes. Men continued their education for career-oriented reasons, while women were seeking more personal goals. Explanations are suggested for male compliance with stereotypes, in aggregate affirming that male nonconformance to defined roles is socially censured. Cette étude compare les traits de caractère, les motifs et les buts de 22 étudiants adultes à ceux de 22 étudiantes du même âge. L'hypothèse formulée énonçait qu'on observerait chez les deux groupe sdes ressemblances entre les objectifs, les raisons pour poursuivre leur formation académique et les obstacles encourus. Cependant, les résultats démontrent que chaque groupe a choisi les buts conformes aux clichésque nous avons pour chaque sexe. Les hommes pousuivaient leur éducation en vue de se préparer pour une carrière tandis que des buts personnels motivaient les femmes. On tente d'expliquer cet acquiescement des étudiants à des attentes stéréotypées en affirmant de façon généraleque la société n'approuve pas que les hommes ne se conforment pas à des rôles déjà bien définis.